2020
DOI: 10.21203/rs.3.rs-18168/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increase in the folate level can decrease the intensity of disorder in patients with depression who use citalopram: a randomized clinical trial

Abstract: Background Depression is one of the most common mental health disorders, which affiliated more than four percent of world population. Several antidepressant agents, including citalopram were developed. High dose and long-term treatment with these agents along with their side effects decrease the treatment adherence. Using supplements such as acid folic is a way to increase these drug’s efficacy. The aim of this study was to assess the effect of acid folic supplement and increase in blood folate level of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Doses of 1 mg/day of folic acid produced no significant changes in the HAM-D scores although it raised the serum level of folate in the intervention group significantly [43]. The increase in serum folate was inversely correlated with a decrease in HAM-D score [43]. Earlier studies have also shown an inverse correlation between serum folate levels and symptoms of depression [52].…”
Section: Folic Acidmentioning
confidence: 82%
See 3 more Smart Citations
“…Doses of 1 mg/day of folic acid produced no significant changes in the HAM-D scores although it raised the serum level of folate in the intervention group significantly [43]. The increase in serum folate was inversely correlated with a decrease in HAM-D score [43]. Earlier studies have also shown an inverse correlation between serum folate levels and symptoms of depression [52].…”
Section: Folic Acidmentioning
confidence: 82%
“…Earlier studies have also shown an inverse correlation between serum folate levels and symptoms of depression [52]. The relationship between dietary folate and depression severity significantly differs by race and ethnicity [43] and baseline levels of folic acid can affect the outcomes in patients without folic acid deficiency [45]. Gender differences in handling folic acid are another factor that might influence the outcomes as the response to folic acid supplementation is more pronounced in females than men [45].…”
Section: Folic Acidmentioning
confidence: 99%
See 2 more Smart Citations